All Days 2009
DOI: 10.2118/121357-ms
|View full text |Cite
|
Sign up to set email alerts
|

Solutions for Better Production in Tight Gas Reservoirs Through Hydraulic Fracturing

Abstract: The challenge to make best producers for the least investment in tight gas reservoirs has always been with the oil and gas industry since production in many tight gas reservoirs is oftentimes marginal, at best. This paper presents solutions for better production in tight gas reservoirs through hydraulic fracturing. Properly engineered hydraulic fracture treatments are enablers to achieve overall economies of scale with development of tight gas reservoirs. These treatments are conducted to byp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…They found that high flow rate or high viscosity created fluid-driven fractures while low rates tended to open the existing NFR. These findings were echoed by Arukhe et al, (2009) who found that many mechanisms contributed to the final created fracture geometry during a hydraulic fracture stimulation including pump rate, viscosity, and proppant scheduling. Damjanac et al, 2010 presented the results of hydraulic fracture modeling in an NFR with a discrete element model (DEM) in which they highlighted the impact of fluid compressibility on hydraulic fracture geometry (a very compressible fluid created a more complex fracture geometry).…”
Section: Hydraulic Fracturing In Naturally Fractured Reservoirsmentioning
confidence: 94%
“…They found that high flow rate or high viscosity created fluid-driven fractures while low rates tended to open the existing NFR. These findings were echoed by Arukhe et al, (2009) who found that many mechanisms contributed to the final created fracture geometry during a hydraulic fracture stimulation including pump rate, viscosity, and proppant scheduling. Damjanac et al, 2010 presented the results of hydraulic fracture modeling in an NFR with a discrete element model (DEM) in which they highlighted the impact of fluid compressibility on hydraulic fracture geometry (a very compressible fluid created a more complex fracture geometry).…”
Section: Hydraulic Fracturing In Naturally Fractured Reservoirsmentioning
confidence: 94%
“…Critical measurements from testing the actual cores has allowed to sift through the chaff to find those "gems" in hydraulic fracturing that materially improve the completion efficiency in tight gas reservoirs. (Arukhe 2009) Develop the Wellbore to Match the Reservoir Potential -"Rightsizing" Solid expandable technology provides the means to establish the largest possible reservoir wellbore to support any type of perforating/fracturing technique without sacrificing maximum stimulation programs, production pathway or future re-entry requirements. The real value added is from the overall wellbore construction.…”
Section: Jet Perforatingmentioning
confidence: 99%
“…To some degree, there has always been production from unconventional reservoirs in virtually all North American basins in the United States such as Rocky Mountains, South and East Texas, north Louisiana, Mid continent, Appalachia, Jonah/Pinedale, Natural Buttes, Wilcox Lobo, Cotton Valley/Travis Peak, and Clinton/Medina. (Arukhe 2009) Estimates of shale gas in the US range from 500 to 1,000 Tcf, while the Gas Technology Institute calculates ~780 Tcf. The US Energy Information Administration estimates that US shale's contain 55.42 Tcf in recoverable gas.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, the technique of hydraulic stimulation has received considerable attention in both renewable and fossil energy sector. Advancements in hydraulic stimulation technology have not only elevated the estimates of energy production from tight gas reservoirs (Arukhe et al 2009) or Enhanced Geothermal Systems (EGS) (Brown et al 2012), but also has important implications for managing CO 2 storage performance (Fu et al 2017). In the field of geothermal energy, hydraulic stimulation is employed for permeability enhancement, in otherwise low porous and low permeable rocks, whereby, fluid is injected at high pressure into the deep-seated, hot and dry rocks activating the natural fracture network or creating new fractures.…”
Section: Introductionmentioning
confidence: 99%